Critical point study in the Sabah power grid for cascading failure blackouts - Moris, Alexsteir (2014)
Sabah System Grid is made up of 66kV, 132kV and 275kV which link up all major towns in Sabah and Federal Territory of Labuan. As the Grid Owner, SESB is responsible for the development, management and operation of the Sabah System Grid. All activities pertaining to the System Grid are bounded by the Sabah and Federal Territory Labuan Grid Code. As demand grows, the network also gradually becomes larger, the transmission line are now operated closer to their limit. As a result, the networks are more vulnerable to the disturbance than before. In April and May 2012, two blackout events took place successively in the power grid of Sabah, which led to the major blackout. Currently, faulty issues in the system can lead to the cascaded failure to the system grid. These issues also can affect the rotor angle of generation motor and cause a loss of generation in the system grid. In this project, the conceptual of Sabah system grid was design for simulation purposes. Then, the identified potential point to be the weakest point was further study. The overall of Sabah system grid is designed and simulated using a PSSE. After that, the potential location to be the weakest point in the Sabah Grid is simulated and analyse. Based on the study conducted, the 132kV northern grid and 275kV interconnection between west coast and east coast is the weakest point in the Sabah system grid. In addition, both interconnections are source from the same substation which is Kolopis substation. Loss of Kolopis substation can lead to the total blackout of Sabah system grid. Finally, the weakest point in the Sabah system grid was successfully identified.